2019
DOI: 10.1371/journal.pone.0221903
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of different molecular and serological methods for detection of Xylella fastidiosa in blueberry

Abstract: Bacterial leaf scorch, caused by Xylella fastidiosa , is a major threat to blueberry production in the southeastern United States. Management of this devastating disease is challenging and often requires early detection of the pathogen to reduce major loss. There are several different molecular and serological detection methods available to identify the pathogen. Knowing the efficiency and suitability of these detection techniques for application in both field and laboratory conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
(71 reference statements)
4
25
0
Order By: Relevance
“…The amplified products could be visualized using SYBR ® Green I nucleic acid gel staining, gel electrophoresis or real-time amplification by Genie ® III (Figures 2-4) as in previous reports [36,57]. Taken together, these results suggest that LAMP is a good substitute for conventional PCR and other PCR-based methods like qPCR due to its simplicity and rapidity without the need of sophisticated instruments for on-site detection of pathogens [52,53]. In conclusion, the LAMP assay developed in this study is an efficient, reliable, and sensitive method for rapid detection of CuLCrV.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The amplified products could be visualized using SYBR ® Green I nucleic acid gel staining, gel electrophoresis or real-time amplification by Genie ® III (Figures 2-4) as in previous reports [36,57]. Taken together, these results suggest that LAMP is a good substitute for conventional PCR and other PCR-based methods like qPCR due to its simplicity and rapidity without the need of sophisticated instruments for on-site detection of pathogens [52,53]. In conclusion, the LAMP assay developed in this study is an efficient, reliable, and sensitive method for rapid detection of CuLCrV.…”
Section: Discussionsupporting
confidence: 73%
“…Currently, the preferred method to differentiate the identity of the virus from other begomoviruses is PCR [3,5,6,12]. However, PCR is not sensitive enough compared to other molecular methods, is laborious and time-consuming, and requires a well-equipped laboratory, which makes this assay unavailable for detecting pathogens in field conditions [52,53]. The LAMP assay described here is a more rapid, accurate, sensitive, simple, and portable diagnosis method, which can be utilized in laboratory and field conditions for timely detection of this virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of LAMP and qPCR were identified to be higher than conventional d i a g n o s t i c m e t h o d s f o r A l t e r n a r i a s o l a n i a n d Phytophthora infestans detection from potato, tomato, and other related host plants (Okiro et al 2019;Khan et al 2018;Lees et al 2019). The real-time PCR has previously also been identified as the most sensitive method, followed by LAMP assay, to detect the Xylella fastidiosa pathogen from blueberry (Waliullah et al 2019). However, both LAMP and qPCR-based diagnostic methods require technical expertise to perform and interpret the test results, and also require high initial investment costs (Notomi et al 2015;Tomlinson 2013;Pirc et al 2009;López et al 2009;Stöger et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) is a novel technique that can overcome many of the limitations of traditional microscopy and molecular PCR based diagnostic assays [1720]. LAMP has shown that the sensitivity can be 100 to 1,000 times higher than conventional methods and can easily detect below 1pg/µl or lower concentration [21]. This method costs less time per sample and is simpler to perform than other detection methods.…”
Section: Introductionmentioning
confidence: 99%